Building equity from the ground up: a community-academic model in Seward County, Kansas - Kara Knapp; Clarissa Carrillo Martinez; Clarissa Carrillo Martinez; Sarah Foreman; Susan Lukwago; Julie Foster; Kay Burtzloff; Vicki Collie-Akers; Katherine Atcheson; Sarah Finocchario-Kessler; Sarah Finocchario-Kessler; Christina M. Pacheco; et al. (Frontiers in Public Health)
BackgroundAcademic-community partnerships are vital to addressing health disparities, particularly in rural and diverse communities. This case study highlights a partnership between the Liberal Area Coalition for Families (LACF) and the University of Kansas Medical Center (KUMC) formed through the Communities Organizing to Promote Equity (COPE) initiative. Located in Seward County, Kansas—a region marked by cultural diversity, linguistic complexity, and high social vulnerability—this collaboration leveraged community strengths and academic resources to co-develop and implement equity-driven strategies.MethodsThe partnership established a Local Health Equity Action Team (LHEAT) composed of community members, stakeholders, and public health professionals, supported by a Regional Community Lead (RCL) and Community Health Workers (CHWs). The LHEAT addressed barriers to food access, COVID-19 testing and vaccination, and sustainable public health services through inclusive bilingual engagement models, culturally relevant services, and data-informed planning. Within two years, the LHEAT grew to over 50 members, launched 33 initiatives, and met nearly 90% of 647 identified client health needs.DiscussionLessons learned emphasize the importance of beginning with local assets, adapting strategies to context, and building trust over time. The LACF-KUMC partnership showcases how community-led coalitions, supported by responsive academic institutions, can drive upstream systems change. This model underscores the need for flexible, sustained investment in local leadership and participatory evaluation to foster resilience, improve health outcomes, and promote equity across underrepresented communities.